Faktor Gaya Hidup yang Berhubungan dengan Hipertensi di Puskesmas Sudiang - Adimas Buyar Alif; Irmawati Irmawati; Apdiyani Toalu; Rahmawati Azis (Jurnal Kesehatan Amanah, 2025)
Hypertension is a major public health problem worldwide that can lead to severe and life-threatening complications such as stroke, heart disease, kidney failure, and other cardiovascular disorders if not properly managed. This study aimed to analyze in greater depth the relationship between obesity, physical activity, and sleep patterns with the incidence of hypertension in the working area of the Sudiang Health Center in Makassar City. A quantitative approach with a cross-sectional design was employed to ensure a comprehensive overview of the risk factors. A total of 100 respondents were selected from a population of 22,572 people using the Slovin formula with a ten percent margin of error and purposive sampling based on predetermined inclusion criteria. Data collection was conducted using structured questionnaires combined with medical records to increase the accuracy of the information obtained. The collected data were analyzed using the Chi-Square test with a significance level set at 0.05. The results showed a significant relationship between obesity (p = 0.000), physical activity (p = 0.023), and sleep patterns (p = 0.019) with the incidence of hypertension. Respondents who were obese, performed low levels of physical activity, and had poor sleep patterns were more likely to develop hypertension. This study highlights the importance of maintaining an ideal body weight, increasing regular physical activity, and improving sleep patterns. Health professionals are expected to strengthen education, counseling, and regular monitoring to control modifiable lifestyle risk factors within the community effectively.